Empowering Rural Sustainability: Advancing Household-Scale Biogas Reactor Technology with Fiber Reinforced Plastic (FRP) in Suntenjaya Village, Lembang - Parapat, Riny Yolandha; Sudaryanto, Bima Aji; Firdaus, Muhammad Zaki; Hidayat, Windy Nur Ramadhani Putri; Kurniawan, Ronny; Yuono, Yuono; Harjaya, Immanuel Teja (Institut Teknologi Nasional, Bandung, 2024)
Rural communities require appropriate technology to process livestock waste that has been polluting the environment, particularly water bodies such as rivers. Biogas technology offers a solution by converting waste into renewable energy, namely biogas, which can be utilized for daily needs and high-quality organic fertilizer production. Unfortunately, the biogas reactors currently in use were developed over 50 years ago without significant innovations. Hence, there is a pressing need for a more efficient (affordable and user-friendly) and effective (in terms of performance) biogas reactor technology suitable for rural communities—specifically, the Fiber Reinforced Plastic (FRP) biogas reactor technology. The objective of this endeavor is to create a household-scale prototype FRP biogas reactor, designed according to specific requirements and standardized for widespread use. This prototype will be implemented and tested in the field, allowing for dissemination to a broader audience. For modeling purposes, the FRP reactor design will be applied in a demonstration plot in Sunten Jaya Village, Lembang Subdistrict, West Bandung Regency. The results from the demonstration plot reveal that the produced biogas amounts to 40 L/kg of cow dung.